Kuliah Kerja Nyata Mahasiswa Universitas Negeri Padang Pada Masa Pandemi Covid-19 di Koto Malintang Tanjung Raya Kabupaten Agam - Aqlaqul Kharimah; Ideal Putra; Fatmariza Fatmariza; Junaidi Indrawadi (Jurusan Ilmu Sosial Politik, Fakultas Ilmu Sosial, Universitas Negeri Padang, 2023)
This study examines the implementation of the Community Service (KKN) program by students from the University of Negeri Padang (UNP) during the period of 2021-2022. The research focuses on the KKN activities conducted in Koto Malintang, Agam District, amid the challenges posed by the COVID-19 pandemic. A qualitative research approach was employed, utilizing observation, interviews, and documentation studies as data collection techniques. Triangulation was used to ensure the validity of the data. The findings of this research indicate that: 1) the KKN program in Koto Malintang involved providing educational initiatives to the community, specifically through technology training at the Aisyiyah Orphanage and monitoring progress through a dedicated application, and 2) various obstacles were encountered during the implementation of KKN, including limited facilities and infrastructure, budget constraints, difficulties in mapping remote tourist attractions for research purposes, and the limitations on direct interaction between KKN students and the community due to the risk of virus transmission.